Negative life events and stress sensitivity in youth’s daily life: an ecological momentary assessment study - Rauschenberg, Christian; Schulte-Strathaus, Julia Clara Catharina; van Os, Jim; Goedhart, Matthieu; Schieveld, Jan N. M.; Reininghaus, Ulrich (Social psychiatry and psychiatric epidemiology, 2022)
Negative life events (LEs) are associated with mental health problems in youth. However, little is known about underlying mechanisms. The aim of the study was to investigate whether exposure to LEs modifies stress sensitivity in youth’s daily life.